Properties of ceramic membranes obtained from kaolinitic clay mixed with palm and mango wastes from Cameroon: Application to wastewater treatment from breweries - Yacouba Mfomboum Kouotou; André Njoya; Ibrahim Cherif Mountapbeme; Saliou Njuhou; Pelagie Syapnjeu Kamgang; Mohamed Mouafon; Dayirou Njoya; Daniel Njopwouo (International Journal of Ceramic Engineering & Science)
Abstract This work focuses on the development of new ceramic membranes based on mixtures of low‐cost and locally available raw materials such as kaolinitic clay and additives such as palm kernel shells and mango seed shells, which are used as pore‐forming agents to increase pore size, and on their efficiencies in rejecting organic and inorganic pollutants from brewery wastewater. The physical and chemical properties of raw materials were characterized via X‐ray diffraction, scanning electron microscopy, differential thermal analysis/thermogravimetry, energy dispersive X‐ray, and Fourier transform infrared spectrophotometry. Sintering was performed at 1100°C, and the permeability and mechanical properties of circular membranes were determined. The membrane filtration operation was used to assess the physicochemical parameters of the wastewater. The membrane composed of 85% kaolinite and 15% mango seed shells showed the best performance. The effective treatment of the breweries wastewater reduced the level of contamination by organic pollutants in the discharge water, with a reduction in concentration from 700 to 14 mg O2 L‒1 of chemical oxygen demand and 250 to 06 mg O2 L‒1 of biological oxygen demand for 5 days, representing elimination rates of 98% and 97.6%, respectively. The treated water is alkaline, with a reduction in pH from 10.79 to 7.77. Suspended matter, turbidity, and electrical conductivity had removal rates of 88%, 90.6%, and 99.8%, respectively. A significant reduction in the salinity of this wastewater contributed to sodium and chloride ion rejection rates of 93% and 79%, respectively, which is an important result for good reuse of the treated water in agriculture and domestic work.